Dynamics of Nitrogen Mineralization by Organic and Inorganic Amendments Through Enzyme Activity of Microbial Community in Laboratory Incubation - Md.Tariful Alam Khan; Md. Billal Hossain Momen; Md. Rashedur Rahman Tanvir; Md. Robiul Islam (Universitas Sebelas Maret, 2025)
Chemical fertilizers provide an immediate nitrogen supply but require repeated application at critical growth stages; however, excessive chemical fertilizer application harms the environment. In contrast, organic fertilizers release nitrogen gradually for a long time, and microbial fertilizers enhance nutrient availability. This study investigated the effects of integrating chemical nitrogen (CN), poultry manure (PM), and microbial fertilizer (MBF) on soil nitrogen availability and microbial activity. Eight treatments were applied: T0 (control), T1 (100% CN), T2 (100% CN + MBF), T3 (75% CN + 25% PM + MBF), T4 (50% CN + 50% PM + MBF), T5 (25% CN + 75% PM + MBF), T6 (100% PM + MBF), and T7 (100% PM). Soil nitrogen fractions, microbial biomass, enzyme activities, and phospholipid fatty acid (PLFA) composition were analyzed. Integrated treatments improved nitrogen availability compared to sole CN application, with T4 showing the highest NO₃–N accumulation. Additionally, T4 increased total nitrogen, organic carbon, and microbial biomass, enhancing soil fertility. Enzymatic activities, including urease, catalase, invertase, and cellulase, responded positively to the integrated treatments, reflecting improved soil health. PLFA analysis revealed shifts in microbial community composition, highlighting the role of PM in promoting microbial diversity and biomass. These findings highlight that blending 50% CN and 50% PM with MBF balances immediate and sustained nitrogen release while stimulating microbial diversity and soil enzyme functions and improves overall soil health, making it a promising strategy for sustainable soil fertility management and reducing chemical fertilizer dependency.